Pengaruh Iklim Organisasi dan Kemampuan Kerja Terhadap Komitmen Organisasional dan Dampaknya Pada Kinerja Pegawai DISPERINDAGKOP dan UKM Kota Pontianak - Mailisa, Yessi; Hendri, M. Irfani; Fauzan, Rizky (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2016)
This research aims to determine the effect of organizational climate and work ability towards organizational commitment and its impact on the employee performance. Endogenous variable in this research is the performance of employees, while, the exogenous variables are the organizational climate and work ability. This research proposes organizational commitment to be the intervening variable. This research using a 55 samples who are taken from the employees of Perindagkop and SMEs in Pontianak City. The type of research was a descriptive survey research with questionnaire as the   main data collecting media. Method of sampling in this research is census method where the entire population being sampled. Data were analyzed using path analysis (Path Analysis) facilitated by SPSS for Windows 22.0. The results showed that the organizational climate and the ability to work in a positive and significant effect on organizational commitment and the performance of employees. In contrast, the variable organizational commitment has no significant effect to employee performance. It means that organizational commitment to the organization of the Perindagkop and SMEs Pontianak City has no effect on employee performance improvement.